Study on Transfer Effort-Performance Expectation (TEPE) the transfer of training effectiveness : a case of private organization / Siti Sofiyah Hj Zainal - Hj Zainal, Siti Sofiyah (Faculty of Business and Management, 2017)
There is a need to determine the factors transfer of training effectiveness has an impact on employee’s Transfer Effort-performance Expectation (TE-PE). This study examines the Factors Transfer of Training: A Case of Private Organization. The study covered a sample of 148 respondents drawn from a total population of 216 employees in SAJ Holdings Sdn. Bhd. Muar. The sample was selected through convenient sampling techniques. Primary data was collected through the use of questionnaires. Data analyses that have been used in this research study are Pearson Correlation analysis, and Multiple Regression analysis. From the findings of Pearson Correlation analysis, all independent variables(Learner Readiness (LR), Motivation to Transfer (MT), Personal Capacity to Transfer (PCT) and Performance Self Efficacy (PSE))are significantly related to Transfer Effort-Performance Expectation (TE-PE).In addition, Learner Readiness (LR) is the influence variable with Pearson correlation is 0.367**, that related to Transfer effort- Performance Expectation (TE-PE). Finally, the most important independent variable in the regression model was Motivation to Transfer (MT) as it had the highest Beta value of 0.380. The study found out that Factors Transfer of training Effectiveness (Motivation to Transfer, Personal Capacity to Transfer, and Performance Self-Efficacy)affects Transfer Effort-Performance Expectation (TE-PE) levels among employees in SAJ Holdings Sdn. Bhd Muar. Where both independent and dependent variables move in the same direction. It indicates that proper independence variable of Motivation to Transfer (MT), Personal Capacity to Transfer (PCT) and Performance Self-Efficacy (PSE) brings more positive effect and vice versa for the employees.